Obesity intervention on the healthy lifestyle in childhood: results of the PRESTO (PrEvention STudy of Obesity) Study (Italian Journal of Public Health, 2008)
Background: Due to increasing problems with childhood and adolescent obesity in Austria PRESTO (PrEvention STudy of Obesity) created a school based intervention program for promoting a healthy lifestyle in Austrian youth.Methods: PRESTO was carried out by a multi-disciplinary team including a physician, a psychologist, a nutritionist and an exercise physiologist. The study was carried out in 12 first grade school classes in Austria (2002-2004), mainly in Vienna (N=260). The control group consisted of 231 subjects. Medical examinations were performed and the participantsf knowledge on good nutrition and dietary habits were collected. Twelve nutrition sessions, one hour per week in each class, were conducted. Teachers were advised to discuss health issues in their classes and specific exercise physiologists were informed about how to integrate appropriate exercises into their lessons.Results: In comparison with control group, classes who performed PRESTO showed a significant knowledge of nutrition, consuming less unhealthy foods. These effects could be observed in the short term (14 weeks) and at follow up (10 months). 24% subjects could be classified as being overweight (BMI .90.Perc.).Conclusions: School-oriented intervention programs/studies, like PRESTO, are a potential way to demonstrate positive effect on nutrition, physical activity and healthy behaviours in youth, especially if carried out on a long-term basis. Ultimately PRESTO has proven to be a suitable programme to be disseminated onto schools throughout Austria.
Keywords: Prevention; children; obesity